Temperature modulating sand-consolidating cyanobacterial biomass, nutrients removal and bacterial community dynamics in municipal wastewater. (April 2020) - Wu, Li; Qian, Long; Deng, Zhikang; Zhou, Xiaolong; Li, Bolin; Lan, Shubin; Yang, Lie; Zhang, Zulin
Highlights: S. hyalinum can well adapt to wastewater and achieve a high biomass production. " S. hyalinum -wastewater bacteria" system efficiently removed wastewater nutrients. An asynchronization between nutrients exhaustion and the halt of growth were found. The "invaded" inoculum significantly regulated native bacterial community. Abstract: Cultivating sand-consolidating cyanobacteria using wastewater has unique advantages on both nutrients recycling and ecological restoration by transferring excessive nutrients from wastewaters to desert areas. Although previous study showed that sand-consolidating cyanobacterium well adapted to synthetic domestic wastewater, no study has been carried out on actual wastewater. This study aims to investigate the sand-consolidating cyanobacterial biomass production and nutrients removal by cultivating Scytonema hyalinum in the municipal wastewater under different temperatures. The results showed that biomass accumulation increased with temperature from 20 ℃ to 30 ℃, while severely depressed at 35 ℃. More than 81.63% sCOD, 90.64% TDN and 97.08% TDP were removed by day 30 under each temperature except for 35℃. The inoculation of S. hyalinum strongly regulated the native wastewater bacterial community. These results indicated that sand-consolidating cyanobacterium S. hyalinum well adapted to municipal wastewater and temperature had remarkable effects on cyanobacterial biomass accumulation, nutrients removal and wastewater native bacterial community dynamics.